HAK EKONOMI DAN HAK MORAL KARYA CIPTA POTRET DI SOSIAL MEDIA - Suka Asih K.Tus, Desyanti (Institut Hindu Dharma Negeri Denpasar, 2019)
Copyright is an exclusive right which contains economic rights and moral rights. Portrait is part of a protected creation. In a portrait that is distributed offline or online through social media, namely economic rights and moral rights that must be presented and adhered to by users. Copyright infragement that still occur for portraits on social media are related to violations of economic and moral rights. The use of portraits on social media without permission for commercial purposes is a form of violation of economic rights. While the form of violations of moral rights over portraits is not to include the creator or source of portraits used in social media. The regulation and protection of economic and moral rights of portraits on social media are regulated in the Copyright Law. Economic rights are stipulated in Article 12 to Article 15. Moral rights are stipulated in Article 5 to Article 7.